2010
DOI: 10.1007/s10549-010-0789-z
|View full text |Cite
|
Sign up to set email alerts
|

The pan-DAC inhibitor LBH589 is a multi-functional agent in breast cancer cells: cytotoxic drug and inducer of sodium-iodide symporter (NIS)

Abstract: International audienceNew drugs with anti-tumor activity, also able to modify the expression of selected molecules, are under evaluation in breast cancer which is becoming resistant to conventional treatment, or in metastatic disease. The sodium-iodide symporter (NIS), which mediates iodide uptake into thyroid cells, and is the molecular basis of radioiodine imaging and therapy in thyroid cancer, is also expressed in a large portion of breast tumors. Since NIS expression in breast cancer is not sufficient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
5
15
1
Order By: Relevance
“…The present report follows our previous observation in breast cancer cells where we observed a potent cytotoxic activity of LBH589 in both estrogen-sensitive and -insensitive cells (16). Our present data demonstrate that LBH589 induces E-cadherin gene expression in aggressive TNBC cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present report follows our previous observation in breast cancer cells where we observed a potent cytotoxic activity of LBH589 in both estrogen-sensitive and -insensitive cells (16). Our present data demonstrate that LBH589 induces E-cadherin gene expression in aggressive TNBC cells.…”
Section: Discussionsupporting
confidence: 92%
“…The appearance of E-cadherin in MDA-MB-231 cells treated with LBH589 could be due to the reactivation of ERα pathway in TNBC cells since other DCI were reported to act similarly in several studies. For example, DCI in association with demethylating agents like 5-aza-2'-deoxycytidine were shown to reactivate ERα expression in ER-negative breast cancer cells (22,39,40); the DCI valproic acid was demonstrated to enhance the efficacy of the anti-estrogen tamoxifen through increasing ER-mediated transcription (16) and also to induce ERα, PR, pS2 and FoxA1, giving to MDA-MB-231 cells an estrogen-sensitive 'phenotype' and restoring their sensitivity to anti-estrogen therapy (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast to the study by Gupta et al 11 in diffuse and large B-cell lymphoma in which panobinostat effectively inhibited mTORC1 and underlines the divergences that can occur between different cell lines. As previously reported in other cancer types, 22,23 panobinostat induced a cell-cycle arrest in G 2 /M in HL cell lines. Moreover, the combination of panobinostat with everolimus was also more effective to induce this cell-cycle arrest in G 2 /M than the use of panobinostat alone.…”
Section: Discussionsupporting
confidence: 86%
“…Other stimulators, such as prolactin, insulin, and insulin growth factor (IGF)-I and II, are able to increase NIS mRNA levels in MCF7 cells also in the absence of RA [66]. Fortunati and coworkers reported that the HDAC inhibitor LBH589 significantly induced NIS mRNA and protein levels as well as iodine uptake in several BC cell lines [67]. Table  3 summarizes the data regarding the stimulation of iodide uptake in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%